Functionalized Sawdust-Derived Cellulose Nanocrystalline Adsorbent for Efficient Removal of Vanadium From Aqueous Solution - Zulu, Bongiwe; Oyewo, Opeyemi A.; Sithole, Bruce; Leswifi, Taile Y.; Onyango, Maurice S. (Frontiers in Environmental Science, 2020)
Water quality degradation due to noxious heavy metals has become a serious concern because of their impact on human health and the ecosystem. In this study cellulose nanocrystal (CNC) derived from sawdust as a green renewable and sustainable resource was functionalized and used as adsorption media to remove vanadium(V) from aqueous solution. The physicochemical properties of the adsorbent were studied using various characterization techniques such as Fourier transform infrared (FTIR) spectroscopy, scanning electron microscopy (SEM), and X-ray diffraction (XRD). The performance of the functionalized CNC adsorbent was explored as a function of solution pH, temperature, adsorbent mass, time and initial concentration in batch adsorption. X-ray diffraction results confirmed the crystalline nature of the CNC. The SEM micrograph revealed rough surface and high porosity, which suggested that the CNC possessed prerequisite properties of a good adsorbent. From the FTIR spectra results the interaction between anionic vanadium species and functionalized CNC was confirmed by the reduction in wavelength of carboxylic groups (–COOH) of the CNC. Meanwhile, from the adsorption results, V removal efficiency was found to be affected by solution pH, temperature, adsorbent mass, and initial concentration. The Langmuir maximum adsorption capacity was 37.9-47.2 mg/g in the temperature range studied. In evaluating the reusability of the CNC through adsorption-desorption studies, results confirmed that the functionalized CNC could be used more than once but with a reduction in affinity of V in each adsorption-desorption cycle. More studies using environmental water samples are therefore still required to explore the robustness of the functionalized CNC adsorption media.